Comparison of Tenth-Grade Students’ Understanding Concept of Motion Between Domino and Snake and Ladders Media - Hermansyah, Hermansyah; Yahya, Fahmi; Astuti, Wahyu Indah Widya; Sentaya, I Made; Sulindra, I Gusti Made (Department of Physics Education, Universitas Mataram, 2023)
Physics learning should be student center. Students used as learning centers impact their understanding of the material or concepts being taught. However, students do not get to learn like that. It impacts students’ low level of understanding of physics concepts, especially the concept of motion. An alternative solution to this is using dominoes and ladders in physics learning. This study examines the effect of using two learning media (dominos and ladder snakes) on the understanding of physics concepts of class X students at MAN 1 Sumbawa. This type of research is quasi-experimental with a posttest-only design. The research sample was obtained using a purposive sampling technique. The number of research respondents was 138 students, who were divided into two experimental groups. Experimental Group 1 used domino media, and Experimental Group 2 used snakes and ladders media. The data collection instrument used was a concept understanding test in the form of filling in and multiple choice given after the treatment was given. The results showed that the domino group better understood the concept than the snakes and ladders group. The parametric prerequisite test shows that the students’ conceptual comprehension data is homogeneous and not normally distributed. The hypothesis test results show that the data’s significance value is less than 0.05. It can be concluded that there are significant differences in understanding the concept of motion between the domino group and the snakes and ladders group. Applying the domino game in physics learning is better than the snakes and ladders game in maximizing the students’ understanding of the concept of motion in MAN 1 Sumbawa.